Increasing Awareness of Future Teachers About Health, Health Preservation and Health Saving Technologies Of Preschool Children - S.S. Sayfieva (Researchparks Publishing, 2022)
This article discusses the issues of awareness of future educators about health, health saving and health-saving technologies for preschool children, as well as their knowledge about the rules of safe life.